Measurements of the charm jet cross section and nuclear modification factor in pPb collisions at root sNN=5.02TeV - (:unkn) unknown (ELSEVIER, 2017)
The CMS Collaboration presents the first measurement of the differential cross section of jets from charm quarks produced in proton-lead (pPb) collisions at a nucleon-nucleon center-of-mass energy of root sNN= 5.02 TeV, as well as results from charm quark jets in proton-proton (pp) collisions at root s=2.76and 5.02TeV. By comparing the yields of the pPb and pp collision systems at the same energy, a nuclear modification factor for charm jets from 55 to 400GeV/cin pPb collisions at root sNN=5.02 TeV of R-pA= 0.92 +/- 0.07 (stat) +/- 0.11(syst) is obtained. This is consistent with an absence of final-state energy loss for charm quarks in pPb collisions. In addition, the fraction of jets coming from charm quarks is found to be consistent with that predicted by PYTHIA 6 for pp collisions at root s=2.76 and 5.02TeV, and is independent of the jet transverse momentum from 55 to 400 GeV/c. (C) 2017 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Heavy ions; Charm-tagging; Heavy-flavor; QUARK-GLUON PLASMA; PB COLLISIONS; HEAVY QUARKS; RECONSTRUCTION; PERSPECTIVE